Global research status and frontiers on microvascular invasion of hepatocellular carcinoma: A bibliometric and visualized analysis - He, Tao; Zou, Jieyu; Sun, Ke; Yang, Juan; Lei, Tingting; Xu, Lin; Liu, Jinheng; Yin, Sineng; Li, Guangkuo (Frontiers in Oncology, 2022)
Introduction:Over the past decade, several studies have been published regarding the microvascular invasion (MVI) of hepatocellular carcinoma (HCC).However, although these publications have had a remarkable impact on MVI, they have not been quantitatively analysed. Therefore, a more comprehensive understanding of the field is needed now. This study characterised the evolution in HCC-MVI research and systematically evaluated scientific outputs using bibliometric citation analysis. Methods:We conducted a systematic search on the Web of Science Core Collection on 2 May 2022 to retrieve studies related to HCC-MVI published between 2013 and 2022.Then, Citespace, VOSviewer and other visualisation tools were used to conduct a bibliometric analysis of the publications. Results:We identified 1208 articles on MVI in HCC. Of these, while China (n = 518) was the most prolific country, Fudan University (n = 90) was the most notable institution. Furthermore, we observed that while Lau Wan Yee participated in most studies (n=26), the Frontiers in Oncology (IF2020:6.24) published the highest number of documents (n = 49) on this subject, with 138 publications. The paper “Bray F, 2018, CA-CANCER J CLIN, V68, P394” also presented the highest co-cited references, with 119 citations. Additionally, the top three keywords were “survival”, “recurrence” and “microvascular invasion”. Moreover, the research hotspots and frontiers in HCC-MVI for the last three years included imaging characteristics and TACE therapy studies. Conclusion:This study comprehensively summarised the most significant HCC-MVI documents from past literature and highlighted key contributions made to the advancement of this subject and the advancement of this field over the past decade. The trend of MVI research will gradually shift from risk-factors and prognosis studies to imaging characteristics and TACE therapy studies.